The unexpected gecko: A new cryptic species within Urocotyledon inexpectata (Stejneger, 1893) from the northern granitic Seychelles - Lobón-Rovira, Javier; Rocha, Sara; Gower, David J.; Perera, Ana; Harris, D. James (Zootaxa, 2022)
Urocotyledon inexpectata, a small gecko endemic to the granitic islands of the Seychelles, has previously been demonstrated to comprise two highly distinct clades based on mitochondrial and nuclear DNA sequences, with one lineage exclusive to a northern group of islands, and the second lineage exclusive to the more southerly islands. Here we complement the genetic data with additional analyses to determine if the clades should be considered distinct species. We present and analyse new morphological data, including skull and jaw osteology, and supplement the available genetic data with DNA sequences for individuals from the previously unsampled island of Felicité, which cluster with the other northern island samples. Despite the high morphological similarity between Urocotyledon populations from northern and southern islands, diagnostic characters were identified, with the northern lineage having a more completely ossified skull, more tooth loci on maxilla and dentary, shorter hindlimbs, relatively smaller eye diameter and relatively wider head. We therefore describe the northern lineage as a distinct species, Urocotyledon norzilensis sp. nov., and discuss the biological and conservation management implications of this taxonomic action.